The Modified Glas-Mosel Formula for Numerical Investigation of the Fusion Cross-Sections of (O-16)+(Ge-70,72,73,74,76) - A Preliminary Study - Yacobus Yulianto; Zaki Su'ud (Department of Physics, Sebelas Maret University, 2023)
Many intense experimental and theoretical studies have been performed to understand the behavior of fusion reactions, especially related to the barrier height of the interacting nuclei. This preliminary study would discuss a variation of the applicability of the Glas-Mosel formula with a little bit of modification applied to heavy systems. The modified Glas-Mosel formula has been utilized to calculate the fusion cross-sections of (O-16)+(Ge-70,72,73,74,76). To perform the differential and the optimization numerics, the Finite Difference and Nelder-Mead methods were applied to Fortran script-code respectively to assist the computational process. Referring to the obtained results, it can be indicated that the obtained results are in positive agreement with the experimental data. In addition, the modified Glas-Mosel formula proposed in this study has the capability to explain the experimental results or in predicting the fusion cross-section of nuclei. Further investigations are needed to get the crucial data to serve as a basic reference.